Peran Pengasuh dalam Inovasi Kepemimpinan di Pondok Pesantren Al-Roudloh Bahrul Ulum Tambakberas Jombang - Iqbal Maulana Al Husnin, Mohammad; Khoirur Roziqin , Muhamad; Faridl Darmawan, Moh. (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This study aims to examine the role of the caregiver (pengasuh) in leadership innovation at Pondok Pesantren Al-Roudloh Bahrul Ulum Tambakberas Jombang and its impact on enhancing the religiosity of the students (santri) and the surrounding community. Employing a descriptive qualitative approach with a case study method, data were collected through observation, in-depth interviews, and documentation. The findings reveal that the caregiver plays a central role in shaping the students' character through an approach that emphasizes role modeling, discipline, and independence. Leadership innovation is implemented through openness in activities that develop students’ potential and character formation based on traditional pesantren values. The main challenges include the young age of most students and the need to preserve the pesantren’s cultural heritage. Positive impacts of this leadership innovation are reflected in a more systematic management of the pesantren and increased student engagement in community activities. The study concludes that the charisma and leadership strategies of the caregiver significantly contribute to shaping an adaptive pesantren education system that remains rooted in traditional Islamic values.